Confirmed population of European bladdernut (Staphylea pinnata) on Radych Mt. (Outer Eastern Carpathians, Ukraine) - Andriy Novikov; Łukasz Piechnik; Mariia Sup-Novikova (Інтродукція Рослин)
In May 2025, after 145 years, we successfully confirmed a population of rare and relic species, European bladdernut (Staphylea pinnata), on Mt. Radych (Outer Eastern Carpathians) near the village Rozheve, Sambir district, Lviv Region (Ukraine). The collected materials are deposited at the LWS herbarium.